Análisis biomecánico de los miembros inferiores de una persona de movilidad restringida grado IV usando una silla bipedestadora con una capacidad de carga de 100 kg - Flores Mugmal, Tatiana Gabriela (2015)
This project has the purpose of showing a biomechanical analysis of the lower limbs of a person with restricted mobility degree IV, however it is necessary to carry out an anthropometric analysis of a sample of patients and an ergonomic analysis of the wheelchair that many people will use. The biomechanics allows to associate the laws of mechanical motion with the lower limbs, with special emphasis in the system muscle- skeletal. This document covers four chapters: First chapter contains all the issues on disability and fundamental concepts of the system muscle- skeletal focused on the lower limbs, to understand the area of medical sciences. It was necessary to perform various measurements of the human body with a sample of nineteen people with various diagnoses, this procedure is known as Anthropometry and together with the analysis of the results of the sample is precisely detailed in chapter two. Third chapter deals with the biomechanical analysis with the respective calculations, graphs, charts, and simulations. For this, Autodesk Inventor Professional 2015 and Autodesk ForceEffect Motion were used. Fourth chapter considers the Ergonomics, a multidisciplinary science that is closely related to Anthropometry and its purpose is the adequacy of products to meet the needs of users for the benefit of health. Finally, the conclusions and recommendations of the work are presented.